Semiotic Analysis of the Song Kawanen Saur Composed by the Musical Group Jepang Jowo - Zulfa, Novita Hana; Sinaga, Syahrul Syah (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the lyrics of the song "Kawanen Saur" using a Peircean semiotic approach, focusing on understanding the signs contained in the lyrics and how these lyrics reflect the life experiences and cultural values of Indonesian society, especially during the month of Ramadan. The results of the analysis show that the lyrics of this song describe a person's concrete experience, especially the difficulty of waking up in the morning, through a combination of representamen, objects, and interpretants that produce a deep understanding of the behavior and situations experienced by the individual. The lyrics also describe the struggle between physical needs, social norms, and religious morality, by showing the internal conflict that arises due to the difference between desires and applicable rules. In addition, this analysis reveals that the lyrics function as a representation of Indonesian culture, by describing the experience of breaking the fast and conveying a profound moral message. Through the elements of representamen, objects, and interpretants, a humorous and reflective meaning is created that not only provides entertainment but also reflects a culture rich in spiritual and social values. In conclusion, the lyrics of the song Kawanen Saur not only represent a personal story, but also describe collective values in society, as well as showing the spirit of hard work and the hope for spiritual rewards through dedication and devotion.